2016
DOI: 10.1373/clinchem.2015.241513
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of SPINK1 in Cancer

Abstract: BACKGROUND Tumor-associated trypsin inhibitor (TATI) was originally isolated from the urine of a patient with ovarian cancer. It was later shown to be produced by many other tumors and several normal tissues. It had earlier been isolated from the pancreas and was hence called pancreatic secretory trypsin inhibitor (PSTI). It belongs to a family of protease inhibitors presently called serine peptidase inhibitor Kazal type (SPINK). In the SPINK family TATI/PSTI is SPINK1, which is the name used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 77 publications
3
78
0
Order By: Relevance
“…Like IL‐6, SPINK1 has been shown to affect cancer cell growth and motility . Recently, Mehner and coworkers showed that recombinant SPINK1 at concentrations of 10 and 100 nM increased proliferation of ovarian cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like IL‐6, SPINK1 has been shown to affect cancer cell growth and motility . Recently, Mehner and coworkers showed that recombinant SPINK1 at concentrations of 10 and 100 nM increased proliferation of ovarian cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Both IL‐6 and SPINK1 are known to regulate many cellular functions, such as growth, differentiation, and motility . Contradicting results of IL‐6 in colon cancer growth have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1G) levels. Since, SPINK1 overexpression has also been implicated in colorectal, lung, pancreatic, and ovarian cancers (20), we sought to examine if SPINK1 is regulated by a similar mechanism in cancers of different cellular/tissue origins. Thus, we determined the status of SPINK1 expression in multiple cancer cell lines (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, SPINK1 was found to be abnormally expressed in solid tumors, including PCa 4. As a result of this, further studies were devoted to investigating whether this peptide was associated with the prognosis of PCa.…”
Section: Introductionmentioning
confidence: 99%